PERBEDAAN RERATA RASIO KALSIUM MAGNESIUM DAN RERATA RASIO NATRIUM KALIUM SERUM - Serudji, Joserizal; Helga, Helga; Bachtiar, Hafni (Andalas Obstetrics And Gynecology Journal, 2017)
The high incidence of preeclampsia and eclampsia causes the importance of early detection especially eclampsia which is the main cause of maternal morbidity and mortality and bad perinatal outcome. The etiology was unknown, but is related to changes in electrolyte status. Electrolytes such as calcium (Ca2+), Magnesium (Mg2+), sodium (Na+) and potassium (K+) play an important role in pre-eclampsia and eclampsia because they contribute significantly in vascular smooth muscle function. This study was done to analyze the differences in mean levels of calcium magnesium ratio and sodium potassium ratio of maternal serum in severe preeclampsia and eclampsia. We performed an observasional comparative with cross sectional study on 16 women with severe preeclampsia and 16 women with eclampsia who met the inclusion criteria and there were no exclusion criteria. The samples were recruited in Dr. M Djamil general hospital Padang, Solok District Hospital, and Pariaman District Hospital from May 2015 to January 2016. The levels of calcium serum were examined by atomic absorption spectrophotometry (AAS), magnesium levels were examined by enzymatic metode, sodium and potassium levels were examined by ion selection electrode (ISE). The differences in mean levels of calcium magnesium ratio and sodium potassium ratio between the two groups was analyzed by using independent t test. The mean levels of calcium magnesium ratio in severe preeclampsia was significantly higher than eclampsia. The mean levels of sodium potassium ratio in severe preeclampsia was significantly lower than eclampsia.Keywords: Calcium magnesium ratio, sodium potassium ratio, severe preeclampsia, eclampsia